Serum transaminase levels after experimental paracetamol-induced hepatic necrosis. Issue 10 (October 1975) - Dixon, M F; Fulker, M J; Walker, B E; Kelleher, J; Losowsky, M S
Abstract : The relationship between serum transaminase levels and the extent of paracetamol-induced liver necrosis has been investigated in the rat. Three methods of histological quantitation were used to assess of necrosis--arbitrary grading, point counting, and the image-analysis computer. Highly significant correlations were obtained between the three methods and all were found to be reproducible. A close correlation was found between the extent of hepatic necrosis and the serum ASAT and ALAT 24 hours after a large dose (4 g/kg) of paracetamol. Likewise, the mean grade of necrosis correlated reasonably well with the serum enzyme levels in the recovery phase at 36 and 72 hours, although the transaminase level for a given degree of necrosis was considerably lower at 72 hours than at 24 hours. These findings suggest that serum transaminase levels gives a reliable indication of the severity of hepatic necrosis if the time of ingestion of the paracetamol is known and taken into account.